Strategic Indicators for Strategic Intervention in Sports Facilities Management Performance in Malaysia - Mohd Asrul Hassin; Mohd Azian Zaidi; Irwan Mohammad Ali (Journal of Business and Social Review in Emerging Economies, 2022)
Purpose: The accessible sporting facilities are underutilised, being misused, not being protected, and not being maintained by the responsible parties. The majority of studies indicate that sports venues face a variety of facilities management (FM) issues due to the inadequacies of their current operating systems, including the financial aspect, the lack of qualified personnel, the effectiveness and quality of management operations, the optimization of operations, and safety concerns. The purpose of this article is to explore the strategic indicators for strategic intervention targeted at improving the management of sports facilities in Malaysia by identifying the most important aspects.